Generate Electricity by Waste Material - Suhas Bagal; Mahesh Jadhav; Siddharth Jadhav; Vikas Bhopale; Prof. Shende Y.N (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Electricity generation by burning waste materials, also known as thermal waste-to-energy, is a process that involves converting waste materials into electricity by burning them in a combustion chamber. This process is a sustainable solution for waste management as it reduces the volume of waste sent to landfills while producing renewable energy. The methodology for electricity generation by burning waste materials typically involves waste collection, handling, and preparation, incineration, energy recovery, and ash management. The generated electricity can be used to power local communities or industries or fed back into the national grid. The process of electricity generation by burning waste materials provides a reliable source of electricity while reducing greenhouse gas emissions by avoiding the release of methane gas from landfills. Overall, electricity generation by burning waste materials is a promising solution for waste management and renewable energy production. However, it is important to carefully consider the potential benefits and drawbacks of this method and to ensure that appropriate regulations and technologies are in place to minimize any negative environmental impacts.